1982
DOI: 10.1126/science.7146913
|View full text |Cite
|
Sign up to set email alerts
|

Mouse c-myc Oncogene Is Located on Chromosome 15 and Translocated to Chromosome 12 in Plasmacytomas

Abstract: Hybridization studies with viral oncogene probes indicate that c-myc, the cellular gene homologous to the transforming gene of avian myelocytomatosis virus, resides on mouse chromosome 15 and in many plasmacytomas is translocated to the antibody heavy chain gene locus on chromosome 12. The transcriptional orientation of the translocated c-myc sequence is opposite the orientation of the adjacent C alpha gene that codes for the heavy chain of immunoglobulin A. The translocated c-myc sequence is not the same onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(81 citation statements)
references
References 20 publications
2
79
0
Order By: Relevance
“…Adrian C. Hayday, Stephen D. Gillies recently been shown that the c-myc gene is translocated into an immunoglobulin locus in certain lymphoid neoplasms of both mice and men [7][8][9][10][11][12] . Thus, murine c-myc gene is recombined into the immunoglobulin heavy-chain locus in BALBIc plasmacytomas characterized by t(12:15) translocations 7,[9][10][11] .…”
Section: Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adrian C. Hayday, Stephen D. Gillies recently been shown that the c-myc gene is translocated into an immunoglobulin locus in certain lymphoid neoplasms of both mice and men [7][8][9][10][11][12] . Thus, murine c-myc gene is recombined into the immunoglobulin heavy-chain locus in BALBIc plasmacytomas characterized by t(12:15) translocations 7,[9][10][11] .…”
Section: Authorsmentioning
confidence: 99%
“…Thus, murine c-myc gene is recombined into the immunoglobulin heavy-chain locus in BALBIc plasmacytomas characterized by t(12:15) translocations 7,[9][10][11] . Likewise,in a majority of the many Burkitt's lymphomas or non-Hodgkin's lymphomas characterized by t(8:14) (q24; q32) translocations, the c-myc gene is recombined into the immunoglobulin heavy-chain locus 8,11,12 .…”
Section: Authorsmentioning
confidence: 99%
“…The pioneering work of Bishop and colleagues established that v-myc was the oncogene captured by the avian MC29 myelocytomatosis transforming virus (Sheiness et al, 1978;Alitalo et al, 1983). On the heels of this revelation were the discoveries that v-myc's cellular homolog c-Myc (Sheiness and Bishop, 1979;Sheiness et al, 1980;Crews et al, 1982;DallaFavera et al, 1982), as well as other Myc family members N-Myc and L-Myc (Kohl et al, 1983;Schwab et al, 1984;Nau et al, 1985;Seeger et al, 1985), are activated in many cancers. Indeed, the current tally for Myc activation in human cancer now approaches 70%, suggesting that this event is required for tumorigenesis.…”
Section: The Myc Paradoxmentioning
confidence: 99%
“…The etiology of these cancers is not known, but they are probably driven by genomic instabilities in B cells that result in chromosomal translocations or other mutagenic DNA lesions involving proto-oncogenes and tumor suppressor genes. Indeed, many lymphomas harbor chromosomal translocations involving immunoglobulin (Ig) genes (Crews et al, 1982;Dalla-Favera et al, 1982) such as the c-myc/Ig heavy chain (IgH) translocation. To investigate the oncogenic role of c-myc, Em c-myc transgenic (Tg) mice were generated by coupling the c-myc gene with the Ig-m enhancer (Adams et al, 1985).…”
mentioning
confidence: 99%